Cognitive behavioral intervention in the Chinese cultural context: A case report. (3rd July 2013) - Ng, Petrus; Tsun, Angela; Su, Susan; Young, Daniel
Abstract Introduction Depression is predicted to become the world's second leading cause of disability by 2020 according to the World Health Organization. Cognitive behavioral intervention (CBI), recognized as a viable and effective treatment for depression, is becoming more widely used among Chinese clients. However, information about the application of this Western approach in the Chinese population is very limited. Methods This paper discusses adaptations of CBI protocols for Chinese patients, considering the major Chinese cultural characteristics of predestination, losing face, avoiding conflict, and Yin‐Yang balance (PLAY) for persons with depression. Results Illustrated is the application of the PLAY protocol in the actual case of a 35‐year‐old woman with depression. Implications for integrating Chinese cultural characteristics with CBI are discussed. Discussion There is evidence for adaptations of CBI for enhancing its effectiveness among Chinese people within their cultural context. Since there are limited studies on cultural‐sensitive CBI for Chinese people, the conclusions drawn from this study are only preliminary. Further studies that verify the findings reported in this paper are necessary.